2007
DOI: 10.1186/1752-1947-1-78
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Castleman's disease: a case report

Abstract: Castleman's disease is a clinicopathological entity associated with lymphoproliferation. We report a case of a 71 year old gentleman who was initially clinically suspected to have lymphoma (owing to clinical features at presentation), but was later histologically confirmed to have Castleman's disease. This case report underlines the importance of definitive histological diagnosis in patients with lympadenopathic presentation associated with systemic symptoms and the distinctiveness of multicentric Castleman's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…Recent studies have demonstrated that HHV-8 is able to produce an IL-6 homologue, the interleukin responsible for hypergammaglobulinaemia and plasmacytosis seen in multicentric Castleman disease (MCD). [12] The controversy remains regarding whether CD variants are separate entities or are two ends of the same spectrum of disease. CD has an increased prevalence in HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that HHV-8 is able to produce an IL-6 homologue, the interleukin responsible for hypergammaglobulinaemia and plasmacytosis seen in multicentric Castleman disease (MCD). [12] The controversy remains regarding whether CD variants are separate entities or are two ends of the same spectrum of disease. CD has an increased prevalence in HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Two similar cases of hyaline vascular type of multicentric disease in Bangladesh and abroad were managed with steroids resulting in symptomatic relief and disease remission. 12,13 The systemic analysis of patients with Castleman disease by Talat revealed a 78% three-year disease free survival rate for patients with HIV negative multicentric hyaline vascular (and unicentric plasma cell type) variants. 14 The markedly different outcomes and disease associations of the CD variants leaves room for further studies, particularly regarding the modalities of treatment in our country where facilities are often limited.…”
Section: Discussionmentioning
confidence: 99%
“…Castleman’s disease, a very rare lymphoproliferative disorder of unknown cause, was first described over 50 years ago in 1956 by Dr Benjamin Castleman, a pathologist at Massachusetts General Hospital 1 , 2. It was first reported in a group of patients with benign localised hyperplastic lymph nodes 2.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported in a group of patients with benign localised hyperplastic lymph nodes 2. Although the aetiology is not completely understood, the pivotal roles of HHV8 and overproduction of interleukin-6 (IL-6) have been emphasised 1.…”
Section: Discussionmentioning
confidence: 99%